Proposal of a linear equation to determine somatic growth velocity by male Wistar rats’ body mass - Cossio-Bolanos, Marco Antonio (2012)
Introduction: In order to determine the degree of biological maturation in rodents it is necessary to apply non-invasive and invasive methods, for which studies covering different strains of rats need simple procedures to control the confounding effects of biological maturation they may cause. Objectives: To determine from body mass growth velocity of Wistar male rats and to propose linear regression equations to predict growth velocity peak (GVP). Design: Longitudinal cohort study. Institution: State University of Campinas, São Paulo, Brazil, Department of Pharmacology. Methods: From 101 rats 25 male Wistar rats 21 days old were selected in probabilistic-random (randomized tables). Body mass (g) was assessed every week until 16 weeks of life. For statistical analysis, descriptive statistics were used in arithmetic average (X) and standard deviation (SD). To determine significant differences between ages ANOVA for repeated measures was used (p <0.001) and to correlate age variables weight and GVP Pearson (r) was used (p <0.01). GVP prediction was carried out through simple linear regression analysis and multiple stepwise (p <0.001). Main outcome measures: Growth speed; proposal of linear regression equations to predict growth velocity peak. Results: Growth velocity peak assessed by body mass appeared at about 42 days of life. Three equations and multiple linear regression were generated, where determination of (R2) coefficient for model 1 was 0.99, for model 2 0.89 and model 3 0.99, respectively. These equations predicted the proximity and separation of male Wistar rats GVP and results could be interpreted through 14 levels. Conclusions: GVP occurred at 42 days of life and linear regression equations were generated from body weight and age in order to predict somatic maturation degree of male Wistar rats.